Permainan Edukatif Kardus Bekas untuk Mengembangkan Motorik Halus Anak Usia Dini - Aisyah; Hartanti, Jahju; Kinasih, Titah; Masita, Yanita Dwi (Universitas Muhammadiyah Kuningan, 2024)
This research is an experimental study to analyze the improvement of fine motor skills in early childhood. The subjects of this study were children aged 5-6 years, the question used was observation. The data collection methods include: the steps to implement educational games from used materials, tests before the treatment of educational games made from used materials, and after the treatment of making educational games. The data analysis technique used was to determine the differences in the value of each aspect of the pre-test and post-test on the dependent variable (fine motor skills) using the T test. From the results of the t test to determine the effect of educational tools made from used materials on the fine motor development of children aged 5-6 years at TK Permata Ibu Surabaya, there is a difference between the pre and post-test scores. So, there is the influence of the use of educational games from used materials on fine motor skills development in children aged 5-6. The test results show that t count of 20,123 is greater than t-table 2,064 with a significance level of 95%.